Enhanced production of Dopa‐incorporated mussel adhesive protein using engineered translational machineries. Issue 7 (13th April 2020) - Jeong, Ye Seul; Yang, Byeongseon; Yang, Byungseop; Shin, Mincheol; Seong, Jihyoun; Cha, Hyung Joon; Kwon, Inchan
Abstract: Mussel adhesive proteins (MAPs) have great potential as bioglues, particularly in wet conditions. Although in vivo residue‐specific incorporation of 3, 4‐dihydroxyphenylalanine (Dopa) in tyrosine‐auxotrophic Escherichia coli cells allows for production of Dopa‐incorporated bioengineered MAPs ( d MAPs), the low production yield hinders the practical application of d MAPs. This low production yield of d MAPs is due to low translational activity of a noncanonical amino acid, Dopa, in E. coli cells. Herein, to enhance the production yield of d MAPs, we investigated the coexpression of Dopa‐recognizing tyrosyl‐tRNA synthetases (TyrRSs). To use the Dopa‐specific Methanococcus jannaschii TyrRS (MjTyrRS‐Dopa), we altered the anticodon of tyrosyl‐tRNA amber suppressor into AUA (MjtRNA Tyr AUA ) to recognize a tyrosine codon (AUA). Co‐overexpression of MjTyrRS‐Dopa and MjtRNA Tyr AUA increased the production yield of Dopa‐incorporated MAP foot protein type 3 ( d fp‐3) by 57%. Similarly, overexpression of E. coli TyrRS (EcTyrRS) led to a 72% higher production yield of d fp‐3. Even with coexpression of Dopa‐recognizing TyrRSs, d fp‐3 has a high Dopa incorporation yield (over 90%) compared to ones prepared without TyrRS coexpression. Abstract : The low production yield of Dopa‐incorporated bioengineered MAPs ( d MAPs) hinders the practical applications of dMAPs. Co‐expression of Dopa‐recognizing tyrosyl‐tRNA synthetases led to the enhanced production yield of d MAPs by overcoming the low translational activity of Dopa.